2016
DOI: 10.3109/0284186x.2015.1117135
|View full text |Cite
|
Sign up to set email alerts
|

Survival improvements associated with access to biological agents: Results from the South Australian (SA) metastatic colorectal cancer (mCRC) registry

Abstract: Background Randomized controlled trials evaluating biological therapy have shown improvements in survival from metastatic colorectal cancer (mCRC). Subjects in the trials represent a selected proportion of mCRC patients. We have the potential to assess the impact of biological therapy on mCRC outcomes, particularly the effect of bevacizumab, from a population-based clinical registry by comparing two time cohorts with differences in therapy accessibility. Material and methods A retrospective cohort study was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…While this decision was due to patients’ preference (41.4%), finances (14.4%) or other reasons, survival among this group was significantly worse compared with those who received active treatment (6.4 vs 12.1 months, respectively, P < 0.001; Table ). Tomita et al . observed an improved median OS associated with increased access to 1L bevacizumab use; however, the authors also noted that comorbidities, age and tumor location were likely among the factors that deterred use of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…While this decision was due to patients’ preference (41.4%), finances (14.4%) or other reasons, survival among this group was significantly worse compared with those who received active treatment (6.4 vs 12.1 months, respectively, P < 0.001; Table ). Tomita et al . observed an improved median OS associated with increased access to 1L bevacizumab use; however, the authors also noted that comorbidities, age and tumor location were likely among the factors that deterred use of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Cetuximab and panitumumab are third‐line options for patients with RAS ‐wild type mCRC not previously treated with an anti‐EGFR antibody 2,3 . However, data from the Treatment of Recurrent and Advanced Colorectal Cancer (TRACC) database and the South Australian mCRC registry show that anti‐EGFR antibodies are increasingly being used in first‐ or second‐line in Australia 21,22 . For patients with mCRC refractory to all standard therapies, the other subsequent systemic therapy options are trifluridine/tipiracil or regorafenib 2,3 .…”
Section: Practical Guidancementioning
confidence: 99%
“…The ESMO document states that 'Today, the median overall survival (OS) for patients with mCRC being treated both in phase III trials and in large observational series or registries is 30 months and more than double that of 20 years ago'. This statement is true for a few randomized trials including selected patients with molecularly selected tumours [12,13], but is otherwise an exaggeration; it is not seen in general populations [8,[14][15][16]. Progress has been seen also in elderly patients with CRC [17], but especially in octogenarian it is in mCRC limited to a few months in median OS, or from about 2-3 months to 3-6 months [18,19].…”
Section: Editorialmentioning
confidence: 99%
“…Much controversy exists about the importance of adding bevacizumab to chemotherapy in mCRC and how the randomised trial data should be interpreted. Several populationbased studies have shown that patients treated with bevacizumab live longer and do better than patients not receiving bevacizumab [16,36,37]. Such comparisons should always be looked at with some suspicion as bias is always present [38].…”
Section: Should Bevacizumab In the Absence Of Clear Contraindicationsmentioning
confidence: 99%